2019
DOI: 10.1111/fwb.13296
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of increasing nitrogen:phosphorus ratios on zooplankton community composition and whitefish (Coregonus macrophthalmus) growth in a pre‐alpine lake

Abstract: The combination of increasing atmospheric depositions of reactive nitrogen (N) and the highly effective diminishing of external phosphorus (P) loadings can change key nutrient ratios in lake ecosystems. Consequently, ratios of dissolved inorganic N (DIN) to dissolved P (DP) in lakes are increasing. However, potential consequences for aquatic organisms are as yet far from understood. We formulated three hypotheses on the potential effects of rising DIN:DP ratios on a lake food web: (1) increasing DIN:DP ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 81 publications
(150 reference statements)
0
7
1
Order By: Relevance
“…is predicted at seston C:P ratios >300 42 , as it was the case in our experiment. While previous studies have demonstrated increasing P limitation with N enrichment 14,43 , we were unable to detect signs of increasing P limitation with increasing N enrichment, such as increasing seston N:P ratios. Additionally we did not observe any correlation of seston stoichiometry with Daphnia biomass, which does not exclude the possibility that this mechanism could operate supplementary.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…is predicted at seston C:P ratios >300 42 , as it was the case in our experiment. While previous studies have demonstrated increasing P limitation with N enrichment 14,43 , we were unable to detect signs of increasing P limitation with increasing N enrichment, such as increasing seston N:P ratios. Additionally we did not observe any correlation of seston stoichiometry with Daphnia biomass, which does not exclude the possibility that this mechanism could operate supplementary.…”
Section: Discussioncontrasting
confidence: 99%
“…The causal relationship described between N enrichment and reduced biochemical food quality might also be relevant to other lake systems, although the qualitative effects of N enrichment could be masked by the quantitative effects of phytoplankton growth in N limited lake systems 39 and upscaling from mesocosms to lake systems may have its limitations 44 . However, an N related reduction in secondary production could even affect higher trophic levels, such as fish 43 . Cladoceran zooplankton are known to represent the primary food source for planktivorous fish in temperate lakes 45 , and cladoceran production is positively correlated to fish biomass in lakes e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Excess N loading may also favor phytoplankton growth via reducing the fitness and biomass of herbivorous zooplankton (Trommer et al, 2017;Lorenz et al, 2019). For instance, mesocosm experiments found that N addition caused stoichiometric shifts in the biomass of primary producers towards higher N:P and C:P ratios, which lowered cladoceran and total zooplankton biomasses but favored the dominance of rotifers (Lorenz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Excess N loading may also favor phytoplankton growth via reducing the fitness and biomass of herbivorous zooplankton (Trommer et al, 2017;Lorenz et al, 2019). For instance, mesocosm experiments found that N addition caused stoichiometric shifts in the biomass of primary producers towards higher N:P and C:P ratios, which lowered cladoceran and total zooplankton biomasses but favored the dominance of rotifers (Lorenz et al, 2019). In shallow lakes, although P has traditionally been considered the primary nutrient causing harmful cyanobacterial blooms, recent findings from laboratory studies and lakes throughout the world demonstrate that N can be important in controlling the timing, density, and toxicity of some nondiazotrophic cyanobacterial blooms (reviewed by Gobler et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the traditional context of ecological stoichiometry theory and nutrient limitation, attention has largely been focused on the general N:P supply ratio in ecosystems. The subject of N addition in N-excess systems has rarely been directly investigated (Poxleitner et al 2016;Trommer et al 2017;Lorenz et al 2019). Lakes are naturally co-limited by N and P, or are seasonally limited by either of the two nutrients (Elser et al 2007;Sterner et al 2008;Paerl et al 2016).…”
Section: Introductionmentioning
confidence: 99%